The house that Lou built - Respicio, Mae (New York : Wendy Lamb Books, 2018)
Longing for an escape from her extended Filipino family, Lou plans to build a tiny house on land she inherited from her father, but difficulties quickly arise.
Ages 8-12.
Keywords: Children's stories; Domestic fiction